Operando phase mapping in multi-material laser powder bed fusion - Shieren Sumarli; Florencia Malamud; Steven Van Petegem; Steve Gaudez; Antonios Baganis; Matteo Busi; Efthymios Polatidis; Christian Leinenbach; Roland E. Logé; Markus Strobl (Virtual and Physical Prototyping)
Layer-wise laser-based additive manufacturing techniques offer immense versatility and flexibility in fabricating metallic composites with complex shapes. Interest in producing new multi-materials with advanced characteristics outpaces the available methods that provide insights into the bulk material formation, which in turn enables process and material optimisation. While some advanced operando studies enable highly local observations in the established metallic layers, the effect of intrinsic heat treatment inherent in the process in the bulk of the material is generally beyond reach of operando characterisation. Here, we approach the regime through advanced operando neutron imaging utilising a custom-designed laser powder bed fusion device on a neutron beamline. Operando polarisation contrast neutron imaging experiments were carried out during building centimetre-sized specimens with different powder premixture compositions of 316L and CuCrZr. The results of these full-field spatially resolved measurements reveal the quantitative evolution of ferromagnetic phases and temperature throughout the specimens and processing time.